TDRD5 binds piRNA precursors and selectively enhances pachytene piRNA processing in mice - Ding, Deqiang (Nat Commun, 2018)
Pachytene piRNAs are the most abundant piRNAs in mammalian adult testes. They are generated from long precursor transcripts by the primary piRNA biogenesis pathway but the factors involved in pachytene piRNA precursors processing are poorly understood. Here we show that the Tudor domain-containing 5 (TDRD5) protein is essential for pachytene piRNA biogenesis in mice. Conditional inactivation of TDRD5 in mouse postnatal germ cells reveals that TDRD5 selectively regulates the production of pachytene piRNAs from abundant piRNA-producing precursors, with little effect on low-abundant piRNAs. Unexpectedly, TDRD5 is not required for the 5′ end processing of the precursors, but is crucial for promoting production of piRNAs from the other regions of the transcript. Furthermore, we show that TDRD5 is an RNA-binding protein directly associating with piRNA precursors. These observations establish TDRD5 as a piRNA biogenesis factor and reveal two genetically separable steps at the start of pachytene piRNA processing.